Evidence and practices of the use of next generation sequencing in patients with undiagnosed autosomal dominant cerebellar ataxias: a review - NOVIS, Luiz Eduardo; SPITZ, Mariana; JARDIM, Marcia; RASKIN, Salmo; TEIVE, Hélio A. G. (Arquivos de Neuro-Psiquiatria, 2020)
Autosomal dominant cerebellar ataxias (ADCA) are heterogeneous diseases with a highly variable phenotype and genotype. They can be divided into episodic ataxia and spinocerebellar ataxia (SCA); the latter is considered the prototype of the ADCA. Most of the ADCA are caused by polyglutamine expansions, mainly SCA 1, 2, 3, 6, 7, 17 and Dentatorubral-pallidoluysian atrophy (DRPLA). However, 30% of patients remain undiagnosed after testing for these most common SCA. Recently, several studies have demonstrated that the new generation of sequencing methods are useful for the diagnose of these patients. This review focus on searching evidence on the literature, its usefulness in clinical practice and future perspectives.
Keywords: next generation sequencing; autosomal dominant cerebellar ataxias; spinocerebellar ataxias